(untitled) (Transactions on Additive Manufacturing Meets Medicine, 2019)
Selective laser melting, also known as 3D metal printing or L-PBF, is being increasingly adopted as the manufacturing method of choice for various types of surgical implants and prostheses. They include dental prosthetic components, patient-matched cranio-maxillofacial implants and mass-produced spine and orthopaedic implants. The presentation will address several key technical developments that contribute to the robustness and productivity of the selective laser melting process. The requirements for a medical device manufacturer on machine qualification and process validation will be addressed, as well. Various case studies on SLM production of surgical implants and dental prostheses will be reviewed during the presentation.